Concomitant hypokalemia and hypocalcemia: a very rare but life-threating combination of reversible causes of cardiac arrest - an unusual first manifestation of coeliac disease: coeliac disease-induced cardiac arrest - Silvestri, Ivan; Merigo, Giulia; Bonetti, Claudia; Guerra, Maria B.; Pignatelli, Serena; Stirparo, Giuseppe; Ristagno, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
The causes of cardiac arrest are extremely heterogeneous. Among these, both hypokalemia and hypocalcemia are known reversible factors that can lead to cardiac arrest. In this report, we present a unique case report of a patient with previously undiagnosed coeliac disease who experienced cardiac arrest due a combination of hypokalemia and hypocalcemia resulting from malabsorption. A 66-year-old male presented to the emergency department with symptoms of malaise, weakness, weight loss, and persistent diarrhea. The patient exhibited characteristic signs of hypokalemia and hypocalcemia, including fasciculations, weakness, and swelling. An electrocardiogram showed a normal rhythm, and blood tests confirmed the electrolyte imbalances. Despite initial treatment, the patient experienced sudden cardiac arrest. Prompt resuscitation efforts were successful in restoring spontaneous circulation. However, recurrent episodes of ventricular arrhythmias and cardiac arrest occurred. Large doses of intravenous potassium chloride, in conjunction with magnesium, were needed prior to restore electrolyte balance. The concomitant severe hypocalcemia required caution calcium supplementation, to avoid further decreases in serum potassium levels. Appropriate ion replacements ultimately led to successful resuscitation with good functional recovery. During the hospital stay, the patient was diagnosed with coeliac disease. This case is noteworthy for its uniqueness, as there are no documented instances in the scientific literature linking cardiac arrest directly to coeliac disease. It is important to emphasize the need for investigating potential reversible causes of cardiac arrest, such as hypokalemia and hypocalcemia, and implementing appropriate interventions to address these factors.